2004
DOI: 10.1002/bem.10205
|View full text |Cite
|
Sign up to set email alerts
|

Plant sensitivity to low intensity 105 GHz electromagnetic radiation

Abstract: Exposing seedlings of the flax, Linum usitatissimum L., to a variety of weak environmental stresses followed by a 2 day calcium deprivation, triggers the common response of production of epidermal meristems (actively dividing groups of cells) in the hypocotyl, which is the part of the stem between the root and the cotyledons (the pre-existing leaves in the embryo). This production reaches a plateau of 10-20 meristems after a month in the case of mechanical stimulation and cold shock. Recently, we have shown th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 20 publications
0
24
0
2
Order By: Relevance
“…These depend on a multitude of diVerent (and uncontrolled) factors and are concerned with long-term eVects, thereby lessening the likelihood of a direct cause-eVect relationship (Boice et al 2002;Feychting et al 2005). Plants are rarely used in RF-EMF experiments (Selga and Selga 1996;TaVoreau et al 2002TaVoreau et al , 2004, partly because their very inertia makes the casual observer presume they are insensitive and thus unresponsive to their environment. In fact the opposite is more likely -their inability to escape the environment implies that plants must be able to sense subtle changes and adapt their responses accordingly Ferguson 2004).…”
Section: Introductionmentioning
confidence: 98%
“…These depend on a multitude of diVerent (and uncontrolled) factors and are concerned with long-term eVects, thereby lessening the likelihood of a direct cause-eVect relationship (Boice et al 2002;Feychting et al 2005). Plants are rarely used in RF-EMF experiments (Selga and Selga 1996;TaVoreau et al 2002TaVoreau et al , 2004, partly because their very inertia makes the casual observer presume they are insensitive and thus unresponsive to their environment. In fact the opposite is more likely -their inability to escape the environment implies that plants must be able to sense subtle changes and adapt their responses accordingly Ferguson 2004).…”
Section: Introductionmentioning
confidence: 98%
“…[4][5][6][7][8][9][10][11][12] The response of plants to stimuli involves changes in the level of free calcium in the cytosol and such changes exhibit complex spatio-temporal dynamics. [13][14][15][16][17][18][19][20] Using the model of the induction of epidermal meristems in the hypocotyl of flax seedlings, [7][8][9][10][11] our group has shown that when flax seedlings (a few days in age) were subjected to both an abiotic stimulus and a 1 to 3 day-long depletion of calcium in the nutrient medium, they developed numerous meristems over the following fortnight. [7][8] These abiotic stimuli included a manipulation stimulus, wind, drought stress, cold shock, and low intensity electromagnetic radiation over a wide range of frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Ïðåç ïîñëåäíèòå ãîäèíè íàðàñòâà èíòåðåñúò íà ó÷åíèòå êúì åôåêòèòå íà ÅÌÏ îò ìîáèëíè òåëåôîíè âúðõó ðàñòåíèÿ. Ðåçóëòàòèòå îò ïðîâåäåíèòå èçñëåä-âàíèÿ ïîêàçâàò, ÷å ðàñòåíèÿòà ðåàãèðàò íà òåçè ÅÌÏ êàòî íà ñòðåñîâ ôàêòîð (Beaubois, 2007;Roux, 2008; T. Selga and M.Selga, 1996;Tafforeau, 2004;Tkalec, 2005Tkalec, , 2007Vian, 2006).…”
Section: âúâåäåíèåunclassified